2017
DOI: 10.3390/nu9060547
|View full text |Cite
|
Sign up to set email alerts
|

Direct vs. Expressed Breast Milk Feeding: Relation to Duration of Breastfeeding

Abstract: Background: Studies examining direct vs. expressed breast milk feeding are scarce. We explored the predictors of mode of breastfeeding and its association with breastfeeding duration in a multi-ethnic Asian population. Methods: We included 541 breastfeeding mother—infant pairs from the Growing Up in Singapore Toward healthy Outcomes cohort. Mode of breastfeeding (feeding directly at the breast, expressed breast milk (EBM) feeding only, or mixed feeding (a combination of the former 2 modes)) was ascertained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 21 publications
2
47
0
2
Order By: Relevance
“…The rationales for this choice were based on the fact that breastfeeding at the breast is the norm in Iceland, where national data show a 98% initiation rate of term infants (Directorate of Health, 2012). The other reason was that previous studies have shown that mothers that exclusively express breast milk do so for a shorter time compared with mothers that exclusively feed their infant at the breast (Forster et al, ; Pang et al, ; Pinchevski‐Kadir et al, ). It has also been reported that mothers that combine breastfeeding at the breast and formula feeding have a shorter breastfeeding duration than mothers that exclusively breastfeed at the breast (Holmes, Auinger, & Howard, ).…”
Section: Discussionmentioning
confidence: 99%
“…The rationales for this choice were based on the fact that breastfeeding at the breast is the norm in Iceland, where national data show a 98% initiation rate of term infants (Directorate of Health, 2012). The other reason was that previous studies have shown that mothers that exclusively express breast milk do so for a shorter time compared with mothers that exclusively feed their infant at the breast (Forster et al, ; Pang et al, ; Pinchevski‐Kadir et al, ). It has also been reported that mothers that combine breastfeeding at the breast and formula feeding have a shorter breastfeeding duration than mothers that exclusively breastfeed at the breast (Holmes, Auinger, & Howard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Any breast milk feeding refers to an infant receiving breast milk (either directly at the breast or fed expressed breast milk), with or without non-human milk and/or solids. At 3 months, breastfeeding mothers were asked how their infants were fed breast milk (at the breast, bottle only, and breast + bottle) [26]. Bottle only includes infants who received only breast milk expressed from the breast (either manually or via a pump) by bottle, cup or spoon (very few were fed by cup or spoon).…”
Section: Data Collectionmentioning
confidence: 99%
“…With a growing body of evidence that feeding expressed breast milk might be different from feeding at the breast, this is an important finding. Studies have found that there is higher risk of asthma (17)and childhood obesity (18)(19)(20)with expressed breast milk feeding compared to direct breastfeeding. There are also concerns that only feeding expressed breastmilk could result in shorter duration of breastfeeding (20).In our study,expressed breastfeeding in the first month of life did not make any difference to our 6-month breastfeeding rates, but our study was not designed to answer this question.…”
Section: Discussionmentioning
confidence: 99%